Pengaruh Work Family Conflict Terhadap Stres Kerja Dengan Dukungan Sosial Sebagai Variabel Moderasi (Studi Pada Dinas Perhubungan Sumatera Utara) - Ardha Nasution, Fadilah; Saskia; Tamba, Muller (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research was conducted at the Department of Transportation of North Sumatra with the aim of analyzing the effected of work family conflict on work stres and organizational commitment with organizational support as moderating variable. The population were employees in Dinas Perhubungan of North Sumatra, amounting to 178 people. The sample was taken randomly using the Slovin formula so that the number of samples was 123 respondents. The data source used primary data and data collection techniques, namely giving questionnaires to respondents. The data analysis technique used data quality test, MRA test, classical assumption test and hypothesis testing. Based on the research results obtained, it was stated that partially work family conflict had significant effected on work stres to employees. Social support have significant effected on work stres to employees. Social support have not moderates the effect of work family conflict on work stres to employees. There is a moderated correlation between work family conflict to work stres employee.